2003
DOI: 10.1081/ceh-120017739
|View full text |Cite
|
Sign up to set email alerts
|

Increased Renal Angiotensin II AT1Receptor Function in Obese Zucker Rat

Abstract: Angiotensin II (Ang II) via the activation of AT1 receptors and subsequent stimulation of the tubular sodium transporters increases sodium and water reabsorption in the proximal tubule. An enhanced tubular action of Ang II is implicated in obesity related hypertension; however, the mechanism of such a phenomenon is unknown. Present study was designed to determine the AT1 receptor numbers and function in the proximal tubule of obese and lean Zucker rats. Obese Zucker rats were hypertensive and hyperinsulinemic.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
31
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 39 publications
6
31
1
Order By: Relevance
“…Even before the development of diabetes, ZDF rats have increased pressor responsiveness to Ang II (33). In the kidney, this may be related to increased AT 1 receptor abundance and function (34). Consistent with this finding, expression of AT 1 receptor protein was increased more than threefold in the islets of ZDF rats, correlating with fibrosis and ␤-cell loss.…”
Section: Discussionsupporting
confidence: 74%
“…Even before the development of diabetes, ZDF rats have increased pressor responsiveness to Ang II (33). In the kidney, this may be related to increased AT 1 receptor abundance and function (34). Consistent with this finding, expression of AT 1 receptor protein was increased more than threefold in the islets of ZDF rats, correlating with fibrosis and ␤-cell loss.…”
Section: Discussionsupporting
confidence: 74%
“…18 Similarly, an upregulation of the renal AT 2 receptor function on tubular sodium metabolism was found in streptozotocin-induced diabetic rats, 35 where dopamine D 1 receptors also are shown to be defective. 36 In addition to the defective dopamine D 1 receptor, we 3,11 and others 23 have reported enhanced Ang II function on tubular sodium transport and hyperantinatriuretic activity in obese compared with lean Zucker rats. Compared with the AT 2 receptors, in general, the AT 1 receptors are the predominant receptor subtype; therefore, the net effect of Ang II is believed to be mediated via the activation of the AT 1 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that, on one hand, the renal dopamine D 1 receptor, a natriuretic hormone receptor, function is defective, 18 and on the other hand, Ang II function with an antinatriuretic effect is hyperactive in obese Zucker rats. 11 However, we reported recently that AT 2 receptors are upregulated in the cortical membranes of obese Zucker rats, and on selective activation, the AT 2 receptors (4 lean rats and 6 obese rats); *PϽ0.05 vs basal within the same group (ANOVA followed by Newman-Keuls multiple comparison test). #PϽ0.05 vs lean (Student t test) (B) Effect of CGP42112 (10 nmol/L) on nitrite/nitrate formation in the proximal tubular suspension isolated from lean and obese Zucker rats, in the absence and presence of PD123319 (1 mol/L), and L-NAME (100 mol/L).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental models of diabetes, several abnormalities of blood pressure regulation and sodium handling have been reported (1)(2)(3)(4). It is likely that an overactivity of antinatriuretic factors and a dysfunction in natriuretic factors contribute to sodium retention (5)(6)(7). Dopamine promotes sodium excretion via activation of renal D1 receptors (8).…”
mentioning
confidence: 99%